Perspektif Perlindungan Hukum Bagi Anak Dibawah Umur dalam Perkawinan Usia Muda dan Perkawinan Siri - Hisbah Hisbah (Universitas Batanghari Jambi, 2018)
The young generation of the son as the successor of the nation, has the right and obligation to participate in building the country. The child is the capital of development that will maintain, retain, and develop the results of development. On the other hand these children do not have the ability to complement and develop themselves, carry out rights and obligations as citizens who can afford betanggung responsible and beneficial to each other.